The Characteristics of the Notarial Profession as a Provider of Pro Bono Legal Services For Indigent Communities - Andika Putra Eskanugraha; Widodo Ekatjahjana; Fendi Setyawan (Danadyaksa: Post Modern Economy Journal, 2025)
This study examines the notarial office as both a legal profession and a Public Official as stipulated in the Law on Notarial Office (Undang-Undang Jabatan Notaris/UUJN). The concepts of “profession” and “Public Official” as attached to the Notary have distinctive characteristics within the Indonesian context. As a legal professional, the Notary performs duties professionally to serve the public in the field of private (civil) legal services within the scope of his or her authority. These legal services are remunerated through honoraria paid by members of the public, the amount of which is regulated by the UUJN and the professional organization. In providing legal services to the public, Notaries are obliged to render services free of charge to indigent persons. This obligation is regulated under Article 37 of the UUJN, which also prescribes sanctions for non-compliance. Through the UUJN, the Government facilitates economically disadvantaged members of society to ensure the legal protection of their rights in transactions and legal acts that require authentic evidence in the form of a notarial deed. However, the UUJN does not clearly explain the criteria and requirements for determining who qualifies as an “indigent” person eligible to receive free legal services from a Notary. Furthermore, the prevailing laws and regulations do not specify the types or scope of notarial legal services that may be provided to economically disadvantaged persons under this scheme. Accordingly, the legislation should more carefully regulate the subjects eligible to receive free notarial legal assistance, while still taking into account eligibility requirements, the scope of services that may be provided, and service standards to be applied by Notaries when rendering pro bono legal services to indigent persons.